EFFECT OF LITHIUM CHLORIDE AND SODIUM CHLORIDE ONIONICINTERACTION OF DILUTE SOLUTION IN AQUEOUS BUTANOL (Biological Sciences - PJSIR, 2020)
The '1Scos1tics or LiCI and NaCl solutions for different concentrations in aqueous butanol (0-7°0) mi,..lures al ,·arious lcmpcralurcs were measured The viscosity dala was intcrprcled in terms of ion-solrnnt interactions. A regular mcrcmcm m the v1scosit1cs "11h the mcn:asing conccmrations of sail as well as increasing in percent composition of aqueous butanol mixtures is observed  The ,alues of A & B coeOicients or Jones-Dole equation  have been dctem1ined  gr:1ph1call) .lt \\3S found  that A & B coellic1cnts  ,ary with  concenlrat1on  of LiCJ and  NaCl as \\1th  the composition of  bulllnolmixtun:s and temperatures. The positi, c values of B- coeflicicnt decreased with rise in l.:rnpcralurc led to the conclusion lhat NaCl and LiCI in aqueous butanol mixtures bcha,·c as structure maker whereas. m aqueous medium NaCl ttnd LiCI showing negative  values of B-eoetlicient  behave as structure breakers.An attempt has also been  made to determine the acti,·ation energy ( E,) as a function  of conccntr,1tion of l.iCI and NaCl  in aqucous-butanol mi'ltures. It sho\\ s that actirntion energy is int1ucnccd b the conccnlr:ition of salts and percent composition  of soh·enls.